DETECTION OF SALMONELLA SPECIES AMONG PATIENTS WITH SUSPECTED CASES OF TYPHOID FEVER IN WUDIL GENERAL HOSPITAL (FUDMA JOURNAL OF SCIENCES, 2023)
The prevalence of Salmonella typhi infection among patients with reported cases of typhoid fever in Wudil general hospital was investigated by serological examination of blood samples and by culture method of stool collected from patients attending the Hospital. A total of 140 each of blood and stool samples were analyzed using the method of Widal slide agglutination test and selective cultivation on Salmonella-Shigella (SS) agar respectively. Out of this, 112 (80%) of the samples were found to be positive, while 28 (20%) of the samples were found to be negative for both Widal agglutination test and culture on SS agar. In the study, males were more infected by S. typhi than females. The presence of these organisms among patients with symptoms of typhoid fever is a threat to public health especially if immunocompromised patients are involved. Based on the research findings it can be seen that substantial numbers of reported patients were exposed to predisposing factors for typhoid fever infection. Hence it is recommended that action should be expedited in the provision of safe drinking water to the public; discourage defecation in an open area and the improvement of personal hygiene
Keywords: Salmonella typhi, Typhoid fever, Detection, Patient